Female breast cancer in relation to exposure to medical iatrogenic diagnostic radiation during life - Gledo, Ibrahim; Pranjic, Nurka; Drljević, Kenan; Prasko, Subhija; Drljevic, Irdina; Brzeziński, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Exposure to radiation and aging are the leading causes of breast cancer among female patients. We aimed to investigate and assess the relationship between exposure to medical, diagnostic and iatrogenic radiation and breast cancer using a questionnaire among 100 newly diagnosed female breast cancer patients and 100 control female subjects without cancer. Material and methods : A case control study using a family ambulatory based survey was conducted among 200 female patients from all municipalities of Zenica-Doboj Canton. New cases of breast cancer among subjects of experimental groups (n = 100) were diagnosed between 1 January 2003 and 31 December 2007 using the institutional clinical procedure for breast cancer diagnosis. Data were obtained using a self-rated questionnaire on radiation as a breast carcinogen. Data analysis was performed using SPSS version 19.0. Results : There were no significant differences between the two groups and their subgroups for individual data and demographics except for prevalence of decreased family financial situation (practical poverty) among subjects with breast cancer in relation to control subjects (31%: 17% among control subjects; p = 0.001). Female patients who are exposed to iatrogenic radiation before the 3rd year of life (OR = 1.29; 95% CI: 0.839–1.985) and those who are exposed to CT more than twice per year are more than twice as likely to have breast carcinoma (OR = 2.02; 95% CI: 1.254–3.261) compared to control subjects. Poverty and low family income are vulnerability factors associated with elevated levels of breast carcinoma. This result is not in accordance with prior study results. ConcIusions : It is necessary to develop an adequate registration system of iatrogenic exposure to radiation for each patient of any age, particularly for children aged < 3 years and for CT iatrogenic exposure.